Lipid Perfluorohexane Nanoemulsion Hybrid for MRI-Guided High-Intensity Focused Ultrasound Therapy of Tumors - Liu, Sitong; Hou, Xiuqi; Zhu, Wenjian; Zhang, Fang; Chen, Weiling; Yang, Binjian; Luo, Xin; Wu, Dalin; Cao, Zhong (Frontiers in Bioengineering and Biotechnology, 2022)
Magnetic resonance imaging-guided high-intensity focused ultrasound (MRI-guided HIFU) is a non-invasive strategy of diagnosis and treatment that is applicable in tumor ablation. Here, we prepared a multifunctional nanotheranostic agent (SSPN) by loading perfluorohexane (PFH) and superparamagnetic iron oxides (SPIOs) in silica lipid for MRI-guided HIFU ablation of tumors. PFH was introduced to improve the ablation effect of HIFU and the ultrasound (US) contrast performance. Due to its liquid-to-gas transition characteristic, it is sensitive to temperature. SPIOs were used as an MRI contrast agent. Silica lipid was selected because it is a more stable carrier material compared with normal lipid. Previous studies have shown that SSPNs have good biocompatibility, stability, imaging, and therapeutic effects. Therefore, this system is expected to develop an important therapeutic agent for MRI-guided HIFU therapy against tumors.